2005
DOI: 10.1653/0015-4040(2005)088[0099:nfdrfc]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

New Flight Distance Recorded for Coptotermes Formosanus (Isoptera: Rhinotermitidae)

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 2 publications
1
27
0
1
Order By: Relevance
“…Alate Trapping. This small contribution of the adjacent in ground termite population to the alate capture is consistent with the Þndings of Simms and Husseneder (2009) and Messenger and Mullins (2005) and indicates that Formosan termite alates are capable ßyers that can reinfest locations which have been subjected to area wide termite control strategies.…”
Section: Discussionsupporting
confidence: 88%
“…Alate Trapping. This small contribution of the adjacent in ground termite population to the alate capture is consistent with the Þndings of Simms and Husseneder (2009) and Messenger and Mullins (2005) and indicates that Formosan termite alates are capable ßyers that can reinfest locations which have been subjected to area wide termite control strategies.…”
Section: Discussionsupporting
confidence: 88%
“…Geographical separation of the colonies of the two subpopulations of Maui does not exceed swarming distance (Messenger and Mullins 2005;Husseneder et al 2006;Simms and Husseneder 2009), yet there is little admixture of the colonies. Apparently, interbreeding of Maui colonies is a rare event, as supported by the fact that all simple families in both subpopulations are headed by nestmate pairs, i.e., alates or neotenic pairs from the same colony.…”
Section: Discussionmentioning
confidence: 99%
“…However, the relevant question is not how far termites can fl y but whether swarming distance is sufficient to limit pairing of related alates. Alates of C. formosanus were able to fl y at least 460 m in Japan (Ikehara, 1966) and 892 m in New Orleans (Messenger and Mullins, 2005). Higa and Tamashiro (1983) and Tamashiro et al (1987) concluded a dispersal distance of slightly more than 1 km per year in Hawaii from the fact that C. formosanus took more than 50 years to spread a distance of 64 km on the Island of Oahu.…”
Section: Discussionmentioning
confidence: 99%